Embracing change: from recalibration to radical overhaul for the field of school attendance - Heyne, David; Gentle-Genitty, Carolyn; Melvin, Glenn A.; Keppens, Gil; O’Toole, Catriona; McKay-Brown, Lisa (Frontiers in Education, 2024)
In a world characterized by dynamic demographic shifts, rapid technological transformations, and evolving pedagogical practices, the need for reimagining school attendance and a relationship with education has become paramount. This Research Topic, boldly titled "The Unlearning of School Attendance: Ideas for Change," compels us to challenge conventional thinking and working in this domain. The collection of 12 articles offers compelling opportunities for change, ranging from subtle recalibrations to radical overhauls, depending on the extent to which our current ideas and methods have grown outdated. This opening article serves as a thematic guide, curating the diverse prospects for transformation found within the collection. Four themes encourage us to reconceptualize school attendance and a relationship with education, while another four themes inspire new ways of working in this realm. Furthermore, we explore the pivotal role of the International Network for School Attendance (INSA) in facilitating change, as it strives to foster relationships with education, forge alliances among interested parties, and promote interdisciplinary research. As you engage with this article and the other 12 contributions in this collection, we invite you to reflect on your current ideas and methods, embracing the call for transformative change with compassion and a strong sense of purpose. Together, we can shape a future where school attendance and engagement with learning thrive in harmony with our evolving world.